Plants and mental disorders: the case of Catalan linguistic area - Irún, Laia N.; Gras, Airy; Parada, Montse; Garnatje, Teresa (Frontiers in Pharmacology, 2023)
Mental disorders are among the leading causes of ill-health and disability worldwide. Despite the disease burden they cause, including significant direct and indirect impacts on individual's health and major social and economic consequences in all countries of the world, it is still one of the most neglected areas of public health. In such a context, the medicinal plants traditionally used to pale these pathologies are presented as a promising tool for future drug development for the management of mental health disorders. The aim of the present study is to analyze the information about plant species used to treat mental disorders in the Catalan linguistic area (CLA) and compare these traditional uses with pharmacological literature in order to evaluate the most quoted taxa and their uses and to provide a basis for further research.Data have been recovered from the 'Etnobotànica dels Països Catalans' webpage (https://etnobotanica.iec.cat/) and the meta-analytic work carried out in the present study covers 27 prospections performed in different territories between 1990 and 2019. Descriptive statistics and quantitative ethnobotany were carried out and some ethnobotanical indices were calculated.The number of use reports analysed to treat mental disorders in CLA is 2,544 spread over 183 taxa belonging to 64 families, being the most cited the Malvaceae (29.36% of use reports), Lamiaceae (16.71%), Caprifoliaceae (7.94%), Rutaceae (7.47%) and Papaveraceae (6.01%). The most used taxa to treat or alleviate the mental disorders have been Tilia platyphyllos Scop. (24.53%), Valeriana officinalis L. (7.47%), Salvia officinalis L. (5.07%), Sambucus nigra L. (4.28%), and Ruta chalepensis L. (3.89%). The flowers or inflorescences (47.68%), followed by aerial part (23.49%), have been the most used plant parts, and tisane the most commonly used pharmaceutical form (78.03%). The most reported use is as sedative with 40.92%, followed by anticephalalgic (21.19%) and tranquilizer (20.01%). The informant consensus factor (FIC) was 0.93, and 3.72% was the ethnobotanicity index (EI) value. The information is coincidental with at least one of the comprehensive pharmacological literature sources checked for 73.68% of ethnobotanical uses.